Using finite volume method for simulating the natural convective heat transfer of nano-fluid flow inside an inclined enclosure with conductive walls in the presence of a constant temperature heat source - Ma, Yulin (Elsevier B.V., 2021)
In the present work, natural convective heat transfer of water/Al2O3 nano-fluid in an inclined square enclosure is investigated. The side walls of the cavity are cold and the upper and lower ones are insulated. A wall with a thermal-conductivity of 100 and a thickness of 0.5 is located on the cold walls. Moreover, there is a constant temperature heat source in the center of the enclosure. The enclosure is located under the influence of an inclined magnetic field (MF). The governing equations were solved using the finite volume method (FVM) and solved using the SIMPLE algorithm. The results show that the heat transfer rate intensifies up to 3.11 times with intensifying the Rayleigh number (Ra). The maximum heat transfer occurred at weak magnetic fields. By augmenting the angle of the enclosure, the heat transfer rate on the right and left walls intensifies by 33 and declines by 55, respectively. The heat transfer rate on the right wall intensifies by 14 by augmenting the angle of the MF. The addition of nano-additives also results in intensification in the heat transfer rate. © 2019 Elsevier B.V.